RAGE and TLR4 differentially regulate airway hyperresponsiveness: Implications for COPD. Issue 4 (15th October 2020) - Allam, Venkata Sita Rama Raju; Faiz, Alen; Lam, Maggie; Rathnayake, Senani N. H.; Ditz, Benedikt; Pouwels, Simon D.; Brandsma, Corry‐Anke; Timens, Wim; Hiemstra, Pieter S.; Tew, Gaik W.; Neighbors, Margaret; Grimbaldeston, Michele; et al.
Abstract: Background: The receptor for advanced glycation end products (RAGE) and Toll‐like receptor 4 (TLR4) is implicated in COPD. Although these receptors share common ligands and signalling pathways, it is not known whether they act in concert to drive pathological processes in COPD. We examined the impact of RAGE and/or TLR4 gene deficiency in a mouse model of COPD and also determined whether expression of these receptors correlates with airway neutrophilia and airway hyperresponsiveness (AHR) in COPD patients. Methods: We measured airway inflammation and AHR in wild‐type, RAGE −/−, TLR4 −/− and TLR4 −/− RAGE −/− mice following acute exposure to cigarette smoke (CS). We also examined the impact of smoking status on AGER (encodes RAGE) and TLR4 bronchial gene expression in patients with and without COPD. Finally, we determined whether expression of these receptors correlates with airway neutrophilia and AHR in COPD patients. Results: RAGE −/− mice were protected against CS‐induced neutrophilia and AHR. In contrast, TLR4 −/− mice were not protected against CS‐induced neutrophilia and had more severe CS‐induced AHR. TLR4 −/− RAGE −/− mice were not protected against CS‐induced neutrophilia but were partially protected against CS‐induced mediator release and AHR. Current smoking was associated with significantly lower AGER and TLR4 expression irrespective of COPD status, possibly reflecting negative feedback regulation. However, consistent with preclinical findings, AGER expression correlated with higher sputum neutrophil counts and more severe AHR in COPD patients. TLR4 expression did not correlate with neutrophilic inflammation or AHR. Conclusions: Inhibition of RAGE but not TLR4 signalling may protect against airway neutrophilia and AHR in COPD. Abstract : In mice, the absence of receptor for advanced glycation end products (RAGE) protects against neutrophilia and increased airway reactivity induced by acute smoke exposure, but this protection is largely lost when Toll‐like receptor 4 (TLR4) is also absent. In humans, smoking is associated with lower advanced glycation end product receptor ( AGER ) (encodes RAGE) and TLR4 expression irrespective of chronic obstructive pulmonary disease (COPD) status. AGER gene expression correlates with neutrophilic inflammation and more severe airway hyperresponsiveness in COPD patients. Abbreviations: AGER, advanced glycation end product receptor; COPD, chronic obstructive pulmonary disease; MCh, methacholine; RAGE, receptor for advanced glycation end products; TLR4, Toll‐like receptor 4.